Analisis Metode Tafsir Muhammad Ash-Shabuni dalam Kitab rawâiu’ al-Bayân - Abdur Razzaq; Andy Haryono (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2017)
When tafseer has not become a separate science, then one of the functions of the Messenger of Allah is being in the midst of companions is to clarify the meaning of the Qur'anic verse that is indeed necessary to explain. There are at least two patterns of tafsir development at that time, the first, companions r.a. were reading and listening to the Quran then they understood the laws, second, Messenger of Allah explained the meaning of the Qur'anic verse accordance with the thinking capacity of the Companions. According to some experts, meodel interpretation of the Messenger of Allah. in answering the questions of the Companions-radliyallahuanhum-in those days have not been written. However, at the end of the life of the Messenger of Allah. has begun to be written down. The testimonies of the Messenger of Allah which were not written was feared that would be mixed among the Koran, the hadith and others. This study attempted to understand the rules of exegesis of Muhammad Ash Shabuni in his commentary Rawa'iu al-Bayan fi Tasair Ayat al-Ahkam min Al-Qur'an. By using the literature study approach, this study in addition to revealing the method of interpretation, also describes the findings and contributions of thought that became one of the references in the science of exegesis.